Effect of ruminal versus postruminal administration of degradable protein on utilization of low-quality forage by beef steers - Bandyk, C.A.; Cochran, R.C.; Wickersham, T.A.; Farmer, C.G.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve ruminally fistulated steers were used to evaluate the effects of supplying a highly degradable protein source (casein) both ruminally and postruminally on intake and digestibility of low-quality native hay. Both protein supplementations substantially increased voluntary intake, organic matter digestion, rate of passage, ruminal ammonia, and blood urea concentrations, but intakes were considerably greater when protein was given ruminally as opposed to postruminally.
Keywords: Beef; Intake; Degradable protein; Low-quality forage